2016
DOI: 10.1007/s10384-016-0446-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of granulation tissue formation in lacrimal duct post silicone intubation and its successful management by injection of prednisolone acetate ointment into the lacrimal duct

Abstract: Complication by granulation tissue formation occurred in 10.6 % of the patients who underwent SI for PALDO, yet the injection of prednisolone acetate ophthalmic ointment into the lacrimal passage may have successfully treated the complication without removal of the silicone tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, prolonged intubation might increase the risk of complications, and previous studies have reported that the formation of granulated tissue on the puncta is the most common complication upon detailed clinical examination. 15 , 16 , 17 , 18 , 19 A previous study reported that lacrimal micro-endoscopy revealed that granulated tissue formation can occur not only on the puncta, but also along the entire lacrimal system, which can be caused by infection and/or mechanical stress. 17 In our current case, the granulated tissue might have been caused by inflammatory reaction due to both factors, as it disappeared rapidly after the settlement of dacryocystitis and tube removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged intubation might increase the risk of complications, and previous studies have reported that the formation of granulated tissue on the puncta is the most common complication upon detailed clinical examination. 15 , 16 , 17 , 18 , 19 A previous study reported that lacrimal micro-endoscopy revealed that granulated tissue formation can occur not only on the puncta, but also along the entire lacrimal system, which can be caused by infection and/or mechanical stress. 17 In our current case, the granulated tissue might have been caused by inflammatory reaction due to both factors, as it disappeared rapidly after the settlement of dacryocystitis and tube removal.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 A previous study reported that lacrimal micro-endoscopy revealed that granulated tissue formation can occur not only on the puncta, but also along the entire lacrimal system, which can be caused by infection and/or mechanical stress. 17 In our current case, the granulated tissue might have been caused by inflammatory reaction due to both factors, as it disappeared rapidly after the settlement of dacryocystitis and tube removal. The findings in previous reports, as well as the findings in our current case, suggest that tissue granulation is reversible with proper treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Higher NDO comprising inflammation of sac and duct with large membranous NLD at sac-duct junction was diagnosed from 73.2% of the patients, compared to the lower NDO of membranous obstruction around the Hasner valve [ 56 ]. Injection of prednisolone acetate ophthalmic ointment into the lacrimal passage have successfully treated the complication of granulation tissue formation occurred 10% of NDO patients followed by DE for 12 months [ 57 ]. However, lipogranuloma formation would be also considered after injection of the ointment into the subepithelium layer, which can occur after false passage by blind probing or after laser canaliculoplasty [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the pathological changes of NLD mucosa after silicone intubation have not been clearly elucidated, several studies have suggested that an NLD mucosal inflammatory reaction to silicone material may occur. This reaction can lead to progressive fibrosis, granuloma, or granulation tissue formation [ 18 20 ], eventually resulting in recurrent obstruction of the NLD [ 21 ]. We attempted to maximally expand the NLD mucosal lumen using a sequential dilatation technique and to suppress inflammatory swelling of the NLD mucosa by topical steroids [ 22 ], but a smaller bony NLD may limit the mucosal luminal expansion.…”
Section: Discussionmentioning
confidence: 99%